Comparative study between Pap smear and visual inspection using acetic acid as a method of cervical cancer screening - Begum, SA; Rashid, MH; Nessa, A; Aziz, MA; Zakaria, SM; Roy, JS (Mymensingh Medical Journal, 2012)
Mymensingh Med J. 2012 Jan;21(1):145-150 The abstract of this article is available on the PubMed website